Jackfruit Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi; Ian Maguire (EDIS)
Revised! HS-882, a 13-page illustrated fact sheet by Jonathan H. Crane, Carlos F. Balerdi, and Ian Maguire, provides homeowners with an expanded and reorganized basic reference for growing jackfruit in the home landscape. Tables include information on selected cultivars for Florida, cultural practices by month, fertilizer program, pulp characteristics, and nutritional values. Included in the Master Gardener Handbook. Published by the UF Horticultural Sciences Department, October 2005.